A Transdisciplinary Approach to Student Learning and Development in University Settings - Budwig, Nancy; Alexander, Achu Johnson (Frontiers in Psychology, 2020)
This article considers the opportunities and challenges of transdisciplinary research on student learning in university settings. Fifty years ago, at a meeting in France, the term transdisciplinarity was coined as issues pertaining to the structure of the university and its impact on teaching and learning were considered. We argue that to move beyond what has already been discussed requires added insights from both the learning sciences and developmental sciences. In this article, these two areas are combined with the perspectives of higher education leaders. First, research is considered from the learning sciences on deep learning in relation to university learning and teaching. This body of work illustrates ways students need to be actively engaged in their learning and simultaneously frames teachers as facilitators of students’ constructive efforts rather than disseminators of static knowledge. Second, perspectives from the developmental sciences on processes of development are reviewed, focusing on adolescence and emerging adulthood. Here we highlight the importance of considering developmental systems approaches to aspects of organizing learning at universities in light of extensive research on adolescents and emerging adults. Third, we examine new higher education frameworks that have focused on the importance of student engagement, integration and application of knowledge and the implications of these shifts for organizing higher education learning in more holistic ways that consider disciplines in tandem. In reviewing these three areas, we consider what assumptions are made about the learner, the role of teachers and others in enhancing student learning, and the interaction between learners and contexts where learning takes place. We argue that a full understanding is enriched by consideration of the joint contributions from the learning sciences, developmental sciences, and higher education frameworks.